ANALISIS PROFIL DAN PERKEMBANGAN AKTIVITAS USAHA PEDAGANG DI OBYEK WISATA KOTA BATU - Handini, Darmayanti Pri; Wulandari, Wahju (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The purpose of this study were: (1) To determine the relationship between the merchant profile traders business activities development in tourism Batu (2). To determine the relationship between business profile traders with the development of business activities of traders in the tourist Batu City (3). To determine the development of business-to-income trader traders in tourism in the City of Stone. The population used as samples are traders who move in Stone Town is a tourist attraction in: Selecta, Songgoriti, Java Park, BNS and Stone Town Square and the number of samples defined as respondents were 100 respondents. While data analysis using the Statistical Analysis Descriptive Frequency Distributions and Statistical Analysis Inferential the Chi Square analysis. From the analysis of Chi Square menunjukaan that there is a significant relationship between the level of education, type of traded goods as well as a means of business activity with the development of business activities. Key word:Traders profile, business profile, the development of business activities and operating revenues